Inquiry-Learning-Based module: Improving students’ critical thinking skills in anatomy structure and bacteria physiology materials - Y. Yuhana; M. Maridi; Sri Dwiastuti (University of Muhammadiyah Malang, 2020)
A proper learning media is critically needed in improving students’ critical thinking skill. This research and development aims were: 1) determining the characteristics of inquiry-learning-based module; 2) observing the feasibility of inquiry-learning-based module prototype, and 3) figuring out the effectiveness of the inquiry-learning-based module developedin improving students’ critical thinking on Anatomy Structure and Bacteria Physiology materials. This research and development used 4-D model with four stages, namely: 1) defining; 2) designing; 3) developing; and 4) disseminating. The data analysis technique used were descriptive statistics in term of percentage and inferential statistics i.e. paired samples t-test. The results showed that the module developed was very decent based on the averge scores given by all expert validators (90.73%) as well as education practitioners (91.99%). Moreover, students critical thinking skills was improved by using this module as the t-test analysis results (sig. < .05). Thus, the is suggested to implement inquiry-learning based module to achieve better students’ learning achievement, particularly in Anatomy Structure and Bacteria Physiology materials.